IMPROVING CONCEPTUAL UNDERSTANDING IN QUANTUM PHYSICS THROUGH THE IMPLEMENTATION OF A DIGITAL VISUALIZATION-BASED ARCS-V - Cahyati, Nilam; Supardi; Andriani, Nely; Akhsan, Hamdi; Markos Siahaan, Sardianto (Jurnal Ilmu Fisika dan Pembelajarannya (JIFP), 2025)
Quantum Physics is a compulsory course for Physics students that requires both mathematical and conceptual understanding. A survey of 41 Physics Education students at Sriwijaya University revealed that 85.7% experienced difficulties in learning Quantum Physics. Specifically, 79.5% struggled with formula derivations, 63.6% with problem-solving, and 47.7% with the language used. The Schrödinger equation is one of the most difficult topics as it involves the relationship between wave functions, energy, and probability. This study aimed to develop digital teaching materials based on the ARCS-V (Attention, Relevance, Confidence, Satisfaction, and Volition) motivational approach to support students’ understanding of Quantum Physics concepts. The Rowntree development model was applied, consisting of planning, development, and evaluation stages, along with Tessmer’s formative evaluation, including self-evaluation, expert review, one-to-one evaluation, and small group evaluation. Expert validation results showed a 97.5% (very valid) feasibility level, while student responses in the trial stage reached 89.6% (very practical). The digital visualization of the wave function Ψ(x,t), eigenstates in a one-dimensional potential well, and the |Ψ|² graph effectively helped students relate the Schrödinger equation to the concepts of energy quantization and probability.